Optimized Design and Decision Model Construction of Smart Home Interface for Elderly Users: Integrating Kano-QFD-HCI Methods - Kun Wang; Xuan Liu; Kexiang Li; Qingyi Liu; Zhuang Xiong; Guojie Ji; Jiaxuan Han (Decision Making: Applications in Management and Engineering, 2024)
Under the background of the deep integration of aging society and intelligent technology, the aging-adapted interface design of smart home products has become a key path to improve the quality of life of the elderly. In the interface design and development of smart home appliances, problems such as complex interaction and imprecise transformation of elderly users’ needs often occur. This study proposes a framework that integrates quality function development (QFD) and human-computer interaction (HCI) theory to assist design decisions. The Kano model is used to classify the needs of elderly users in a refined way (basic, aspirational, and excited), and a “user needs-design parameters” quality house model is constructed to realize the quantification of demand priorities and the accurate mapping of design parameters; a multi-dimensional comprehensive evaluation of multiple solutions is carried out by combining the TOPSIS method, and the optimal design is screened out to take into account ease of use, safety, and emotional experience, combined with the TOPSIS method, we conducted a comprehensive evaluation of multiple solutions to select the optimal design solution that takes into account ease of use, safety and emotional experience. The results show that the core needs of elderly users are focused on simplified operation (e.g., one-button start), immediate feedback (e.g., voice prompts), and interface adaptation (e.g., large font, high contrast); the QFD-HCI fusion method can significantly improve the efficiency of requirements transformation and the practicality of design solutions. This study provides theoretical support and practical paradigm for the aging-friendly development and design of smart home products by taking the aging-friendly interface development of smart rice cooker as an example, focusing on exploring the inclusiveness of the elderly group to smart technology and promoting the concept of “technology for the elderly” from concept to realization.